Staphylococcus Derived from Desert and Its Solidified Ability on Aeolian Sandy Soil - Yu Gao; De Yao; Cuiyan Wang; Yanxing Wang; Chi Li (Advances in Civil Engineering)
Many soil microorganisms in nature induce carbonate precipitation, which is used in soil improvement to reduce the pollution of soil environment by traditional chemical improvement. With the goal of expanding the geotechnical applications of biomineralizing bacteria, this study investigated the characteristics of a newly identified strain of soil bacteria, including its mineralization ability, its effect on Aeolian sandy soil, and biomineralization crust effect in the desert field test. The autogenous mineralized strain was isolated and purified from desert Aeolian sandy soil, and the strain was identified as Staphylococcus using 16SrRNA sequence homology. It is a kind of mineralized bacteria seldom used in geotechnical engineering at present, and it was found to have good mineralization ability; the living conditions of Staphylococcus were optimized. Under the determined amount of bacteria liquid, the amount of calcium carbonate precipitation after the bacteria liquid reacted with different volumes of calcium source solution was studied to determine the appropriate ratio of bacteria liquid and calcium source solution and the molar amount of calcium source solution. This study also investigated the effect of mineralization on the strength of sand and determined the particle size range of sand and suitable bacteria concentration that Staphylococcus can effectively stabilize. Field test results verified desert autogenous Staphylococcus had a good mineralization effect on sand. It was suitable for Aeolian sandy soil crust and improvement. In this paper, the autogenous strain was applied to the surface of the desert for the first time to form an in situ microbial mineralization crust. The research results can provide a theoretical basis for the better application of autogenous strain in the desert.